Structural Changes in the National Economy of Ukraine: Threats and Opportunities - Shuvanov, Andrii (Theory and Practice of Public Administration, 2022)
The article examines the main trends of structural changes in the national economy of Ukraine, in particular by indicators of created added value and employment of the population by types of economic activity. Tendency signs of inefficient structuring of the economy, which is a critical obstacle for the future economic development of the state, have been revealed.An analysis of threats and opportunities in the process of structuring the economy was made according to the trends of changes in the specific weight of products by types of economic activity, which of them deepen the disparities of the national economy, and which are of a constructive nature.The distribution of labor resources by types of economic activity is highlighted, in particular, taking into account the labor intensity of products, labor productivity, and the progressiveness of changes in the population employment structure is determined.The existence of deep structural disproportions of the national economy, which proves its inefficiency, is revealed, and the need to eliminate disparities using the tools of state influence in the course of implementing the structural policy of the innovation-investment model of the economy is substantiated. The inertial scenario of further structural changes can lead to extremely negative consequences for the national economy.